Spatiotemporal analysis of offshore wind field characteristics and energy potential in Hong Kong. (15th June 2020) - He, Junyi; Chan, P.W.; Li, Qiusheng; Lee, C.W.
Abstract: On the basis of a numerical weather prediction (NWP) model with 2-km-spatial and 1-h-temporal resolution in conjunction with observations, spatiotemporal analysis of offshore wind field characteristics and energy potential in Hong Kong is presented in this paper. Three-dimensional variational (3DVAR) data assimilation is incorporated for minimizing errors in modelled wind fields. First of all, 80-m wind fields over the entire domain of Hong Kong are generated from the model simulation for one-year period, and their validity is evaluated using the wind records obtained at eight offshore meteorological stations and buoys. Then the maximum likelihood estimation (MLE) method is implemented to determine the Weibull parameters individually for each model grid point, and the goodness-of-fit of Weibull distribution is also examined. Moreover, spatiotemporal variations of offshore wind field characteristics and energy potential are investigated considering different topographic conditions. Attention is paid to special wind phenomena including monsoons and tropical cyclones. Furthermore, inter-annual analysis of wind power statistics is conducted based on 20-year wind records at three offshore meteorological stations. The results show that the offshore areas of Hong Kong are abundant in wind energy with promising potential to generate 6.46 × 10 6 kWh per year per wind turbine at US0.1076/kWh in the Southeastern Water. Highlights: Perform the first spatiotemporal study of offshore wind energy potential in Hong Kong. Numerical Weather Prediction (NWP) model generates 2-km-resolution wind fields. 20-year observations quantifies inter-annual variability and validate the NWP model. Estimate power statistics at hub height under various temporal scales. Promising potential to generate 6.46 × 10 6 kWh at 0.1076 US/kWh per year per turbine.